ANALYZING PHENOMENA OF TEACHING MATHEMATICS TROUGH PERSPECTIVE OF DIDACTICAL CONTRACT - Fuadiah, Nyiayu Fahriza (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACTThis article is a theoretical study of the didactical contract and theapplication of this theory in teaching analysis, especially theteaching mathematics. Didactical contract is an indispensablesubject in the Theory of Didactical Situation. The Didacticalcontract regulates the responsibilities of teachers and students in alesson that is supported by a didactic situation to achieve thelearning objectives and link the process of adaptation andacculturation. The process of devolution and institutionalization wasthen introduced to relate the dimensions of acculturation andadaptation of educational endeavor even though they were under theresponsibility of the teacher. This contract is an excellent means forteachers in communicating with students in accordance with theachievement of learning at the time. The type and level in thedidactical contract can be used as a theoretical framework inidentifying teaching mathematics so that the quality of mathematicsteaching activities in the classroom can be improved in the futureKey Words: Didactical contract didactical situations teaching mathematics